Rainfall seasonality captured in micromammalian fauna in Late Quaternary contexts, South Africa - Thackeray, J. Francis; Fitchett, Jennifer M. (My University, 2016)
There exists ongoing debate regarding shifts in the latitudinal extent of the southern African winter-rainfall zone throughout the late Quaternary. Fossil proxies which can be related directly to rainfall seasonality have the potential to assist in quantifying these shifts. Relationships between mean monthly temperature and mean monthly rainfall in modern environments are quantified to generate a seasonality index associated with summer- or winter-rainfall. These seasonality indices can in turn be related to percentage occurrences reflecting relative abundances of rodent taxa represented in areas within southern Africa. Such data are used together to obtain an equation from which an index of seasonality in rainfall can be calculated, based on relative abundances of rodents in the modern landscape. The equation is applied to rodents represented in a Late Quaternary faunal sequence at Boomplaas Cave in the south-eastern part of the Western Cape Province. Results confirm that this region experienced a predominantly winter-rainfall regime during the Last Glacial Maximum (LGM), though the amount of rain may have been relatively low for the coldest episodes circa 20,000 cal. yr BP in the Boomplaas palaeo-environments.
Keywords: rainfall seasonality; Last Glacial Maximum; Westerlies; microfauna; southern Africa; late Quaternary